The Dynamics of Implementing Ubudiyah Activities in Shaping the Character of Madrasah Ibtidaiyah Students (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2025)
Character education is a fundamental aspect of Islamic education, particularly at the madrasah ibtidaiyah level, which serves as the foundation for students’ personality development. One strategy employed by madrasahs to foster religious character is the implementation of ubudiyah activities integrated into the school culture. This study aims to analyze the dynamics of implementing ubudiyah activities in shaping students’ character, with particular attention to implementation processes, character-building efforts, and the challenges encountered. This research adopts a qualitative approach using a case study design conducted at MI Bustanul Ulum Jombang. The research participants included the head of the madrasah, Islamic Religious Education teachers, classroom teachers, and students. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings indicate that systematically implemented ubudiyah activities contribute positively to the development of students’ religious character, particularly in terms of discipline, responsibility, and politeness. However, the effectiveness of these activities is constrained by several challenges, including limited teaching personnel, low parental involvement, social environmental influences, and difficulties in managing students’ smartphone use. This study highlights that character education based on ubudiyah requires a supportive and synergistic educational ecosystem to ensure sustainable internalization of religious values.